Global Research on Climate Change: A Bibliometric Analysis of Key Themes and Contributions - Prameswary, Clarrisa Nashira; Kulstuma, Najma Oktavia; Siregar, Al Dyara Zeghesna Vutry; Alfarizi, Bilyanto (INTERNATIONAL CONFERENCE OF ECONOMICS AND BUSINESS, 2025)
Climate change has become one of the most pressing global issues affecting various sectors of life on Earth, including agriculture, health, and the economy. These changes are triggered by human activities that are causing an increase in greenhouse gas emissions, with widespread impacts such as rising global temperatures, melting ice, and increasing natural disasters. Sustainable development, which aims to meet today’s needs without sacrificing the capabilities of future generations, plays a crucial role in addressing the challenges of climate change. Sustainable Development Goals (SDGs) by calling for collaborative global action to mitigate and adapt to the impacts of climate change. This study uses bibliometric analysis to explore research trends related to climate change and sustainable development and to identify research developments, key trends, and collaboration networks between researchers and institutions. Using the tools VOSviewer and R Studio, the study visualizes the relationships between global topics and trends, thus guiding the development of future research in this field. The results are expected to contribute to a more comprehensive understanding of climate change and global efforts to achieve sustainable development.